Proteomics research on forest trees, the most recalcitrant and orphan plant species. - Abril, Nieves; Gion, Jean-Marc; Kerner, René; Müller-Starck, Gerhard; Cerrillo, Rafael M. Navarro; Plomion, Christophe; Renaut, Jenny; Valledor, Luis; Jorrin-Novo, Jesús V. (Phytochemistry, 2011)
The contribution of proteomics to the knowledge of forest tree (the most recalcitrant and almost forgotten plant species) biology is being reviewed and discussed, based on the author's own research work and papers published up to November 2010. This review is organized in four introductory sections starting with the definition of forest trees (1), the description of the environmental and economic importance (2) and its derived current priorities and research lines for breeding and conservation (3) including forest tree genomics (4). These precede the main body of this review: a general overview to proteomics (5) for introducing the forest tree proteomics section (6). Proteomics, defined as scientific discipline or experimental approach, it will be discussed both from a conceptual and methodological point of view, commenting on realities, challenges and limitations. Proteomics research in woody plants is limited to a reduced number of genera, including Pinus, Picea, Populus, Eucalyptus, and Fagus, mainly using first-generation approaches, e.g., those based on two-dimensional electrophoresis coupled to mass spectrometry. This area joins the own limitations of the technique and the difficulty and recalcitrance of the plant species as an experimental system. Furthermore, it contributes to a deeper knowledge of some biological processes, namely growth, development, organogenesis, and responses to stresses, as it is also used in the characterization and cataloguing of natural populations and biodiversity (proteotyping) and in assisting breeding programmes.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21353265
Keywords: Forest tree proteomics; forest trees; Plant proteomics; Woody plants

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation